Retrospective cohort study of the impact of faecoliths on the natural history of acute appendicitis - Mei Sze Lee; Rachel Purcell; Andrew McCombie; Frank Frizelle; Timothy Eglinton (World Journal of Emergency Surgery, 2023)
Abstract Background Despite acute appendicitis is one of the most common surgical emergencies, its aetiology remains incompletely understood. Aim This study aimed to assess the rate at which faecoliths were present in acute appendicitis treated with appendicectomy and whether their presence was associated with complicated appendicitis. Methods All adult patients who underwent appendicectomy for acute appendicitis in a 2 years period (January 2018 and December 2019) at a single institution were retrospectively reviewed. The presence of a faecolith was identified by at least one of three methods: pre-operative CT scan, intraoperative identification, or histopathology report. Patients were grouped according to the presence or absence of a faecolith and demographics, type of appendicitis and surgical outcomes analysed. Complicated appendicitis was defined as appendicitis with perforation, gangrene and/or periappendicular abscess formation. Results A total of 1035 appendicectomies were performed with acute appendicitis confirmed in 860 (83%), of which 314 (37%) were classified as complicated appendicitis. Three hundred thirty-nine (35%) of the appendicitis cases had faecoliths (complicated 165/314 cases; 53%; uncomplicated 128/546; 23%, p < 0.001). The presence of a faecolith was associated with higher complications and a subsequent longer post-operative stay. Conclusion The rigorous methodology of this study has demonstrated a higher rate of faecolith presence in acute appendicitis than previously documented. It reinforces the association of faecoliths with a complicated disease course and the importance in prioritising emergency surgery and postoperative monitoring for complications.